Reference architectural styles for service oriented computing - Dillon, Tharam S.; Wu, Chen; Chang, Elizabeth (Springer, 2007)
Architecting service-oriented systems is a complex design activity. It involves making trade-offs among a number of interdependent design decisions, which are drawn from a range of concerns by various software stakeholders. In order to achieve effective and efficient SOC design we believe a careful study of architectural styles that can form the reference architecture is important. Hence, this paper provides a study of architectural styles for the reference architecture of SOC-based software systems. We propose a classification scheme for the architecture styles. These architectural styles are extracted from existing research projects and industry practices based on our classification scheme. For all those identified styles, we present an evolution trend driven by engineering principles for Internet-scale systems. As a result, this paper moves the first step towards creating a Reference Architecture that can be utilised to provide sensible guidance on the design of Web services application architecture.